Neural Correlates of Facial Emotion Recognition in Non-help-seeking University Students With Ultra-High Risk for Psychosis - Hou, Jiaojiao; Schmitt, Simon; Zhao, Xudong; Wang, Jiayi; Chen, Jianxing; Mao, Ziyu; Qi, Ansi; Lu, Zheng; Kircher, Tilo; Yang, Yunbo; Shi, Jingyu (Frontiers in Psychology, 2022)
Background: Since the introduction of neurodevelopmental perspective of schizophrenia research on individuals at ultra-high risk for psychosis (UHR) has gained increasing interest, aiming at early detection and intervention. Results from fMRI studies investigating behavioural and brain functional changes in UHR during facial emotion recognition - an essential component of social cognition - showed heterogenous results, probably due clinical diversity across these investigations. This fMRI study investigated emotion recognition in a sub-group of the UHR spectrum, namely non-help-seeking, drug-naïve UHR with high cognitive functioning to reveal the neurofunctional underpinnings of their social functioning in comparison to healthy controls. Methods: Two large cohorts of students from an elite university (n1 = 4040, n2 = 4364) were screened firstly with the Prodromal Questionnaires and by surpassing predefined cut-offs then interviewed with the semi-structured Interview for Psychosis-Risk Syndromes to verify their UHR status. Twenty-one identified non-help-seeking UHR and 23 non-UHR control subjects were scanned with functional magnetic resonance imaging while classifying emotions (i.e., neutral, happy, disgust and fear) in a facial emotion recognition task. Results: Behaviourally, no group differences were found concerning accuracy, reaction times, sensitivity or specificity, except that non-help-seeking UHR showed higher specificity when recognising neutral facial expressions. In comparison to healthy non-UHR controls, non-help-seeking UHR showed generally higher activation in the superior temporal and left Heschl’s gyrus as well as in the somatosensory, insular and midcingulate cortex than the control subjects during the entire recognition task regardless of the emotion categories. In an exploratory analysis, in the non-help-seeking UHR group, functional activity in the left STG was significantly correlated with deficits in the ability to experience emotions at uncorrected statistical thresholds. Conclusions: Compared to healthy controls, non-help-seeking UHR show no behavioural deficits during facial emotion recognition, but functional hyperactivities in brain regions associated with this cognitive process. Our study may inspire future early intervention and provide loci for treatment using neural stimulation.